2011
DOI: 10.2174/156720211795495349
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Targeting Form of Docosahexaenoic Acid for Experimental Stroke Treatment: MRI Evaluation and Anti-Oxidant Impact

Abstract: Epidemiologic studies report cardiovascular protection conferred by omega-3 fatty acids, in particular docosahexaenoic acid (DHA). However, few experimental studies have addressed its potential in acute stroke treatment. The present study used multimodal MRI to assess in vivo the neuroprotection conferred by DHA and by a brain-targeting form of DHA-containing lysophosphatidylcholine (AceDoPC) in experimental stroke. Rats underwent intraluminal middle cerebral artery occlusion (MCAO) and were treated at reperfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 31 publications
0
28
0
Order By: Relevance
“…A possibility to bypass this issue would be to accelerate the bioavailability of PUFAs to the brain, by direct injection of free or esterified PUFAs into the brain. A preclinical study in rat demonstrated that an injection of DHA can reduce seizure score within one hour or one day, where three months are needed to reach the same result through the diet [167][168][169]. These promising results could be applied in the future to humans to reduce damages following stroke or reduce seizure events, but further investigations are needed before such clinical trials.…”
Section: Perspectives: Implications For Future Therapeutics Of Endocamentioning
confidence: 99%
“…A possibility to bypass this issue would be to accelerate the bioavailability of PUFAs to the brain, by direct injection of free or esterified PUFAs into the brain. A preclinical study in rat demonstrated that an injection of DHA can reduce seizure score within one hour or one day, where three months are needed to reach the same result through the diet [167][168][169]. These promising results could be applied in the future to humans to reduce damages following stroke or reduce seizure events, but further investigations are needed before such clinical trials.…”
Section: Perspectives: Implications For Future Therapeutics Of Endocamentioning
confidence: 99%
“…When pooling the DHA and AceDoPC r groups it appeared that a significant lowering of oxidative stress occurred, although this was not significant for each group alone. However, the values in the AceDoPC r group were lower than in D102, page 2 of 3 the DHA group (Chauveau et al, 2011). Altogether, these results show that AceDoPC r was more efficient than nonesterified DHA to protect the brain in a post-stroke situation.…”
Section: Acedopc Was More Active Than Dha To Decrease the Post Strokementioning
confidence: 71%
“…Each rat was injected with one micromole of either DHA, or AceDoPC (both bound to rat plasma), as compared to the vehicle (rat plasma), or saline, one hour after stroke induction. The post-stroke brain lesions, assessed by magnetic resonance imaging, significantly decreased in both the DHA and AceDoPC r groups, compared to controls, but such a decrease was higher in the AceDoPC r group (Chauveau et al, 2011).…”
Section: Acedopc Was More Active Than Dha To Decrease the Post Strokementioning
confidence: 77%
“…The lesion sizes due to the initial stroke were stable in rats receiving the plasma alone as a control, while they decreased in rats receiving nonesterified DHA or AceDoPC ® , the decrease being higher in rats receiving AceDoPC ® . Neuroscores also tended to be improved in the AceDoPC ® group (Chauveau et al, 2011). The mechanism of neuroprotection observed remains to be clarified but a reduction of oxidative stress has been suggested.…”
Section: Acedopcmentioning
confidence: 89%